Functional alterations of retinal neurons and vascular involvement progress simultaneously in the Psammomys obesus model of diabetic retinopathy. Issue 10 (10th March 2021) - Dellaa, Ahmed; Mbarek, Sihem; Kahloun, Rim; Dogui, Mohamed; Khairallah, Moncef; Hammoum, Imane; Rayana‐Chekir, Narjess Ben; Charfeddine, Ridha; Lachapelle, Pierre; Chaouacha‐Chekir, Rafika Ben
Abstract: To investigate the progression of diabetic retinopathy (DR) in a new diurnal animal model, we monitored clinically the DR in Psammomys obesus ( P . obesus ) during 7 months using electroretinography (ERG) and imaging techniques. After the onset of DR, all ERG components decreased progressively. In scotopic conditions, by 3‐months of disease progression, the diabetic P . obesus displayed a significant decrease in amplitude of b‐max, b‐wave responses, and mixed b‐waves. While mixed a‐wave decreased between 4 and 7 months. Significant differences of OP2 appeared following 1 month of disease. In photopic conditions, we noticed a decrease in the a‐wave at 2 months, while it took more than 5 months in b‐wave amplitude. The photopic negative response (PhNR) and the i‐wave amplitudes decreased following 4 and 5 months. OP1 and OP2 were the first to be altered and a significant decrease in the amplitude started after 3 months. Finally, 30 Hz‐flicker and photopic S‐cone were impaired after 2 and 3 months, respectively. The assessment of the eye fundus of the retina revealed an abnormal vascular architecture appeared at Months 6 and 7. In addition, we noticed exudates in the superior periphery of the retina at the same stage. The retina thickness showed a significant reduction at Month 7. Our results indicate that the clinical correlates of human DR are present in diabetic P . obesus . The depressed of ERGs, disruption of retinal architecture, and the appearance of exudates may reflect vascular and neuronal damage throughout the retina as are seen in the advanced stages of human DR. Abstract : The diabetic retinopathy in the diurnal rodent Psammomys obesus is manifested by a functional and structural dysfunction. The functional alteration detected by the decrease in the amplitude of the ERG components over time following the diabetic induction. Whereas the structural dysfunction is evinced by the disruption of retinal architecture and the appearance of exudates at an advanced stage of the disease progression as well as the decrease of the retinal thinness.